2014
DOI: 10.1111/jam.12460
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus faecalisstrain LZ-11 isolated from Lanzhou reach of the Yellow River is able to resist and absorb Cadmium

Abstract: Lanzhou reach of the Yellow River is contaminated by heavy metals. Microbial research and remediation is still scarce. LZ-11 is the first strain that is able to resist and absorb Cd(II) isolated from this area and might be a good candidate for future cadmium bioremediation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…These results are similar to the findings by Khan [23]. SEM results revealed that P. shigelloides H5 adapts to high concentrations of cadmium ions in the environment by increasing the volume, which is similar to findings by Wu and Sun [22]. EDX results indicate that the outer membrane of P. shigelloides H5 was involved in the adsorption of heavy metals, as Kim reported [31].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results are similar to the findings by Khan [23]. SEM results revealed that P. shigelloides H5 adapts to high concentrations of cadmium ions in the environment by increasing the volume, which is similar to findings by Wu and Sun [22]. EDX results indicate that the outer membrane of P. shigelloides H5 was involved in the adsorption of heavy metals, as Kim reported [31].…”
Section: Discussionsupporting
confidence: 90%
“…EDX results indicate that the outer membrane of P. shigelloides H5 was involved in the adsorption of heavy metals, as Kim reported [31]. One previous study found that bacteria can transport metal ions into the cells by passive transport or by an outmembrane's Mn 2+ /Zn 2+ /Ca 2+ transporter [22]. The intracellular Cd 2+ can combine with phosphate to perform precipitate, or Cd 2+ toxicity can cause a cadmium efflux pump CzcCBA to efflux Cd 2+ in order to reduce damage [23].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Expression levels of chrA and yieF after 30 min Cr (VI) treatment, copy numbers changes of chrA and yieF after 35 days of chromate incubation, and microbial biomass were assessed via real-time PCR. Reactions were performed on CFX96 TM Real-Time PCR Detection System (Bio-Rad) according to the manufacturer’s instructions ( Wu et al, 2014 ). All genes were analyzed in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…The study of cadmium or arsenic resistance of enterococci has frequently involved isolates from habitats likely to encounter high levels of heavy metal pollution (Järup & Akesson, ). For instance, a strain closely related to E. faecalis isolated from petrochemical wastewater discharges in the Lanzhou reach of the Yellow River in China harbored cadA (and a panel of other heavy metal resistance determinants) whose expression was induced by exposure to cadmium (Wu et al, ). Analysis of enterococci from coastal marine sediments in Italy revealed that cadmium‐resistant isolates were significantly more frequent among those which were also resistant to erythromycin, even though the levels of cadmium were rather low (0.070–0.126 μg/g) (Vignaroli et al, ).…”
Section: Cadmium and Arsenic Resistance In Enterococcus Streptococcumentioning
confidence: 99%